2023
DOI: 10.3390/rs15092298
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Discharge Temperature Retrieval and Monitoring of NPPs Based on SDGSAT-1 Images

Abstract: High-accuracy sea surface temperature (SST) retrieval near nuclear power plants (NPPs) is one of the most significant indicators for evaluating marine ecological environment quality, monitoring the real-time situation of thermal discharge, and supporting planning decisions. However, complex computations, the inaccessible real-time vertical profile of the atmosphere, and the uncertainty of atmospheric profile data increase the error of SST retrieval. Additionally, influenced by their low spatial resolution, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The launch of the Sustainable Development Science Satellite 1 (SDGSAT-1) offered a new approach for identifying industrial heat sources. Among the thermal infrared data types, SDGSAT-1 thermal infrared spectrometer (TIS) data exhibit the highest spatial resolution in civilian use and have been widely applied in tasks such as target detection and monitoring [40][41][42]. Therefore, in this study, SDGSAT-1 TIS data were first introduced to identify industrial heat sources and production areas, aiming to address the issues of the insufficient spatial precision in identifying industrial heat sources and the insensitivity to low-heat emission sources.…”
Section: Introductionmentioning
confidence: 99%
“…The launch of the Sustainable Development Science Satellite 1 (SDGSAT-1) offered a new approach for identifying industrial heat sources. Among the thermal infrared data types, SDGSAT-1 thermal infrared spectrometer (TIS) data exhibit the highest spatial resolution in civilian use and have been widely applied in tasks such as target detection and monitoring [40][41][42]. Therefore, in this study, SDGSAT-1 TIS data were first introduced to identify industrial heat sources and production areas, aiming to address the issues of the insufficient spatial precision in identifying industrial heat sources and the insensitivity to low-heat emission sources.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the thermal infrared sensor possesses imaging capabilities with a 300 km swath and a spatial resolution of 30 m, addressing the low spatial resolution drawback in the thermal infrared spectral range of multispectral sensors. Scholars have used its data to conduct studies related to thermal emissions, but no studies have been found for lithology extraction [ 20 , 21 ]. In response to the current research gap, this paper proposes a method for extracting granite based on SDGSAT-1 TIS data, whereby a granite index based on SDGSAT-1 TIS data is first introduced using band ratio to enhance granite and suppress non-target information.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable Development Science Satellite 1 (SDGSAT-1) launched on 5 November 2021, and its thermal infrared sensor (TIS) with a 30 m spatial resolution is a significant addition of data for Earth observation because of its highest spatial resolution in the civilian field and three-band advantage [28]. It has been widely used for target detection and monitoring, such as ship detection [29,30], sea surface temperature retrieval, monitoring near nuclear power plants [31], and arctic sea ice lead monitoring [32]. Therefore, nighttime SDGSAT-1 TIS data were first introduced to identify IHSPAs and improve the recognition accuracy and granularity of IHSs.…”
Section: Introductionmentioning
confidence: 99%